Probing CP-violating Higgs sectors via the precision measurement of coupling constants - Aoki, Mayumi; Hashino, Katsuya; Kaneko, Daiki; Kanemura, Shinya; Kubota, Mitsunori (Progress of theoretical and experimental physics, 2019)
Abstract We study how the effects of the CP violation can be observed indirectly by precision measurements of Higgs boson couplings at a future Higgs factory such as the International Linear Collider. We consider two Higgs doublet models with softly broken discrete symmetry. We find that by measuring the Higgs boson couplings very precisely we are able to distinguish the CP-violating two Higgs doublet model with a certain type of Yukawa interaction from the CP-conserving one.